Pore Structure Differentiation between Deltaic and Epicontinental Tight Sandstones of the Upper Paleozoic in the Eastern Linxing Area, Ordos Basin, China - Jimei Deng; Huan Zeng; Peng Wu; Jia Du; Jixian Gao; Fei Zhao; Zhixun Jiang (Geofluids)
Research on tight gas reservoirs in the eastern margin of the Ordos Basin, China, has recently become a hot spot. This paper mainly studies the reservoir characteristics of tight sandstone in the north-central area close to the provenance in eastern Linxing. Cast thin section, scanning electron microscopy, high-pressure mercury injection, and X-ray diffraction (XRD) were applied to discriminate the tight sandstone reservoir differences between the Permian Taiyuan and Shanxi formations in the study area. The results show that the deltaic tight sandstones in the Shanxi Formation are dominated by lithic quartz sandstone and lithic sandstone with an average porosity of 2.3% and permeability of 0.083 mD. The epicontinental tight sandstones in the Taiyuan Formation are mainly lithic sandstone and lithic quartz sandstone, with average porosities and permeabilities of 6.9% and 0.12 mD, respectively. The pore type is dominated by secondary dissolution pores, containing a small number of primary pores, and fractures are not developed. The capillary pressure curves of the Taiyuan Formation sandstone are mainly of low displacement pressure, high mercury saturation, and mercury withdrawal efficiency, while the Shanxi Formation sandstone is mainly of high displacement pressure, low mercury saturation, and withdrawal efficiency. The diagenetic evolution of sandstone in the Shanxi Formation is in meso-diagenesis stage A, and the Taiyuan Formation has entered meso-diagenesis stage B. The siliceous cement in the Taiyuan Formation sandstone enhanced the sandstone resistance to compaction and retained some residual intergranular pores. The pore types in the Shanxi Formation sandstone are all secondary pores, while secondary pores in the Taiyuan Formation sandstone account for approximately 90%. The results can be beneficial for tight gas production in the study area and similar basins.